An Identification of Learning Motivation and Learning Outcomes in Vibration, Wave, and Light Materials - Meitaza, Dariah; Wiyono, Ketang; Marlina, Leni; Sriyanti, Ida (Berkala Ilmiah Pendidikan Fisika, 2025)
The research aims to identify the learning motivation and learning outcomes of SMPN 7 Padang students in terms of vibration, wave, and light materials. The research was conducted after the learning occurred. The subjects in this study were 128 students from 4 classes, namely classes VIII.1, VIII.2, VIII.3, and VIII.8. To determine students' learning motivation, researchers distributed questionnaires using a Likert scale, while student learning outcomes were taken from daily assessments at the end of the chapter on vibrations, waves, and light. The results obtained from this research are student learning motivation is classified as moderate, and the category of student learning outcomes is also classified as moderate. Indicators of student learning motivation are (1) the desire and desire to succeed in learning, (2) the existence of encouragement and needs in learning, (3) the existence of hopes and ideals for the future, (4) the existence of interesting activities in learning and (5) the existence of a conducive learning environment while learning outcomes were calculated using the completeness criteria for science lessons on vibration and wave material. Based on the research results conducted at SMPN 7 Padang, the most influential indicator is interesting learning activities. Teachers can increase student learning motivation from moderate to high if they carry out interesting activities. Students with high learning motivation have a greater chance of obtaining better learning outcomes than those with low motivation.